Un gioco di citazioni incrociate: “Giotto dipinge il ritratto di Dante” di Dante Gabriel Rossetti - Veronica Pesce (Parole Rubate, 2022)
The article examines Dante Gabriel Rossetti’s watercolor "Giotto Painting the Portrait of Dante". The painting is the result of several artistic and literary quotations, being originally conceived as an interplay of anecdotes, literary texts, and works of art. While evidently based on "Purgatorio" XI, the painting also to passages in the "Vita Nuova" as well as to frescoes in the Palazzo del Bargello and in Santa Maria Novella that Rossetti was probably familiar with.